Influence of cassava mosaic virus on cassava leaf vegetable quality - Almazan, A.; Theberge, R.L. (1989)
People of Zaire prefer cassava mosaic virus-infected cassava leaves to the healthy leaves for vegetable use. The diseased leaves are believed to be sweeter and more tender. To investigate this claim, leaves from three cassava clones, TMS 50395, TMS 30572 and Isunikankiyan, with disease ratings of one to five, were analysed for total cyanide (free and bound), protein (N x 6.25), total soluble sugars and crude fibre. Total cyanide concentration decreased significantly in the three clones with increasing disease severity; protein also decreased as the disease progressed (P = 0.001). Total soluble sugars and crude fibre content were unrelated to disease rating. (AS).